2010
DOI: 10.1111/j.1742-4658.2010.07777.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of proinsulin C‐peptide oligomeric and amyloid states

Abstract: The formation and structure of proinsulin C-peptide oligomers has been investigated by PAGE, NMR spectroscopy and dynamic light scattering. The results obtained show that C-peptide forms oligomers of different sizes, and that their formation and size distribution is altered by salt and divalent metal ions, which indicates that the aggregation process is mediated by electrostatic interactions. It is further demonstrated that the size distribution of the C-peptide oligomers, in agreement with previous studies, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…For example, amyloid fibrils are formed by amyloid beta Aβ (40–43) [7, 21], tau protein [11], polyglutamine [22], transthyretin [35], α-synuclein [24], prion protein [19], and β 2 -microgulobulin [15]. In addition, it has been recently reported that sequentially non-homologous proteins, insulin [34], proinsulin c-peptide [14], lysozyme [6], calcitonin [8], and myoglobin [3] may form amyloid-like fibrils under certain conditions. These observations imply that amyloid structures are common to the intrinsic structures of various proteins, although the mechanism of their formation is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, amyloid fibrils are formed by amyloid beta Aβ (40–43) [7, 21], tau protein [11], polyglutamine [22], transthyretin [35], α-synuclein [24], prion protein [19], and β 2 -microgulobulin [15]. In addition, it has been recently reported that sequentially non-homologous proteins, insulin [34], proinsulin c-peptide [14], lysozyme [6], calcitonin [8], and myoglobin [3] may form amyloid-like fibrils under certain conditions. These observations imply that amyloid structures are common to the intrinsic structures of various proteins, although the mechanism of their formation is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Further, residues Q9-L12, residues G15-A18 and residues Q22-A25 were all shown to have structural preferences in the NMR-derived ensemble average [13]. It has recently been demonstrated that C-peptide also has the ability, under certain conditions, such as low pH, to form β -sheet structure, resembling amyloid structures [14, 15]. The peptide forms predominantly low-order oligomers [14], but very low concentrations of amyloid-like structures may also form [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that C-peptide also has the ability, under certain conditions, such as low pH, to form β -sheet structure, resembling amyloid structures [14, 15]. The peptide forms predominantly low-order oligomers [14], but very low concentrations of amyloid-like structures may also form [15]. The formation of amyloid structure can be enhanced in the presence of subcritical micelle concentration (CMC) amounts of SDS (at low pH), while SDS in amounts above the CMC, on the other hand, promote a more α -helical structure [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The net effect of insulin resistance and hyperinsulinemia is therefore increased levels of intracellular and extracellular Aβ levels, respectively. Interestingly, recent data suggest that oligomeric C-peptide may promote amyloid states [ 116 ]. Infl ammation with activation of microglia promotes Aβ accumulation and amyloid precursor protein (APP) expression and cleavage increase with oxidative stress [ 117 , 118 ].…”
Section: Amyloid Metabolismmentioning
confidence: 99%